2006
DOI: 10.1093/ajcn/84.4.798
|View full text |Cite
|
Sign up to set email alerts
|

Total energy expenditure in the Yakut (Sakha) of Siberia as measured by the doubly labeled water method

Abstract: Activity levels in the Yakut were lower than those in other subsistence groups, especially the women, and were not significantly different from those in persons in industrialized nations. Persons who participated in more subsistence activities and consumed fewer market foods had significantly higher activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 35 publications
4
64
1
Order By: Relevance
“…The Yakut women were significantly less active than the men, spending almost half the time, 25 fewer minutes, in MVPA during the single day of monitoring compared to men. These results are consistent with a previous study within Yakut of the same community (Snodgrass et al, 2006), other indigenous Siberian populations (Katzmarzyk et al, 1994;Leonard et al, 2002Leonard et al, , 2005, and other indigenous circumpolar populations (Dahl-Petersen et al, 2013b). Women also tended (not significantly) to be at increased risk of clustering of cardio-metabolic risk factors though MVPA was not significantly related to risk factor clustering.…”
Section: Gender Differencessupporting
confidence: 91%
See 1 more Smart Citation
“…The Yakut women were significantly less active than the men, spending almost half the time, 25 fewer minutes, in MVPA during the single day of monitoring compared to men. These results are consistent with a previous study within Yakut of the same community (Snodgrass et al, 2006), other indigenous Siberian populations (Katzmarzyk et al, 1994;Leonard et al, 2002Leonard et al, , 2005, and other indigenous circumpolar populations (Dahl-Petersen et al, 2013b). Women also tended (not significantly) to be at increased risk of clustering of cardio-metabolic risk factors though MVPA was not significantly related to risk factor clustering.…”
Section: Gender Differencessupporting
confidence: 91%
“…In a recent study, duration of self-reported MVPA was found to be significantly over-estimated within Inuit of Greenland (Dahl-Petersen et al, 2013a), consistent with other populations (Celis-Morales et al, 2012;Ward et al, 2005). Yakut adults living in the same village as those in this study were found to be sedentary to moderately active using doubly labeled water (Snodgrass et al, 2006). Discrepancy between self-report and objective measure may be an explanation for the differences in activity levels found between this study of Yakut and other studies of indigenous circumpolar populations that report much higher levels of physical activity.…”
Section: Physical Activity and Sedentary Behaviorsupporting
confidence: 88%
“…If our measurements of RMR are 20% greater than actual BMR (a conservative estimate), BMR in orangutans is approximately 36% lower than that of similarly (Table S1). Open circles and triangle represent orangutan adults and juvenile; gray circle and triangle represent human adults and juveniles in a subsistence/agricultural economy (25); black circle and triangle represent human adults and juveniles in industrial economies (33)(34)(35)(36)(37)(38); gray squares represent other eutherian mammals. "S" indicates three-toed sloths (Bradypus variegates); "H" indicates howler monkeys (Alouatta palliata).…”
Section: Resultsmentioning
confidence: 99%
“…Participants rested in the supine position wearing a face mask attached to a low-flow pneumotach for at least 20 minutes prior to the 10-minute measurement of REE. 18 REE was calculated using the modified Weir equation. 19 Total daily energy expenditure (TDEE) was evaluated over 1 week with the doubly labeled water (DLW) technique.…”
Section: Energy Expenditurementioning
confidence: 99%
“…Isotope abundances were measured for H 2 18 O with automated peripheral devices (Finnigan GasBenchII and H/D device; Thermo Fisher Scientific GmbH, Bremen, Germany) interfaced with isotope ratio mass spectrometry (Delta PlusXP, Thermo Fisher Scientific). 22 2 H and 18 O isotope elimination rates (k H and k O ) were estimated using linear regression to include in calculations for rate of CO 2 production. 21,23 Energy expenditure was calculated by multiplying rCO 2 by the energy equivalent of CO 2 for an assumed respiratory quotient of 0.86.…”
Section: Energy Expenditurementioning
confidence: 99%